MODERASI BERAGAMA DALAM KEARIFAN LOKAL: STUDI PADA SELOKO ADAT JAMBI - Reza Pahlepi; Badarussyamsi; D.I. Ansusa Putra (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2023)
This study discusses religious moderation in the Jambi traditional Seloko. The Jambi traditional seloko is a form of oral literature from the Jambi Malay community which contains various values and messages for the Jambi Malay community. This study focuses on the question, how is the manifestation of religious moderation in the Jambi traditional Seloko and the implementation of religious moderation in the Jambi traditional Seloko. The aim of this study is to voice religious moderation through the Jambi traditional Seloko. This research was carried out using library research. Data was collected through documentation techniques and in-depth Seloko reading. Then the data is analyzed using stages; data reduction, to sort data that is relevant to the research topic, present data and draw conclusions. The results of this study state that religious moderation is manifested and implemented in the Jambi traditional Seloko which contains advice: nationality, tolerance, non-violence, and respect for local culture. This is stated in the Jambi traditional Seloko which has the values: togetherness and solidarity, steadfastness in what is right, courage, deliberation, maintenance of traditions and customs, as well as the beauty of language and art. Apart from that, the implementation of religious moderation is reflected in various Jambi traditional Seloko which contain messages including; justice, balance, wisdom, sincerity, and courage. This can be strengthened by Islamic values, because the Jambi traditional Seloko is built based on the values contained in Islamic law (al-Qur'an and Hadith).